The Influence of Knowledge Management on Employee Performance and Innovative Work Behavior at PT. PBT Site Bukit Asam - Vensi Yeka Isdiani; Ken Ditha Tania (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to analyze the influence of knowledge management on employee performance and innovative work behavior at PT. PBT Site Bukit Asam. A quantitative approach using the census method was used, involving 30 respondents from various departments. Data was collected through a questionnaire with a Likert scale and analyzed using Partial Least Square (PLS) with software SmartPLS version 4.0. The research results show that knowledge management positive and significant effect on employee performance (t = 14.114, p = 0.000) and innovative work behavior (t = 9.465, p = 0.000). Knowledge management facilitates the creation, storage, transfer, and application of knowledge so that employees can work more effectively, efficiently, and innovatively. PT. PBT Site Bukit Asam needs to realize the importance of knowledge management and investing resources to develop and implement the system of knowledge management effective way to improve the quality of human resources and company competitiveness. This research shows the importance of knowledge management for PT. PBT Site Bukit Asam in improving the quality of human resources and competitiveness. It is recommended that companies invest sufficient resources to develop and implement the system sustainably.